[Co/Pd]-NiFe exchange springs with tunable magnetization tilt angle - Nguyen, T. N. Anh; Fang, Y.; Fallahi, V.; Benatmane, N.; Mohseni, S. M.; Dumas, R. K.; Åkerman, Johan (Applied physics letters, 2011)
We investigate exchange coupled [ Co / Pd ] 5 - NiFe thin films. Due to competition between the in-plane shape anisotropy of the NiFe and strong perpendicular magnetic anisotropy of the [ Co / Pd ] 5 multilayer, unique magnetic configurations are achievable. In particular, we explore the out-of-plane magnetization tilt angle of the NiFe layer. Experimental results, based on conventional magnetometry, ferromagnetic resonance, and magnetic force microscopy, agree well with one-dimensional micromagnetic simulations. We find that the tilt angle is highly tunable (0°-60°) over a small range of NiFe thicknesses (4.8-8 nm). Potential applications for high power, zero-field operation spin torque oscillators are discussed.